2017
DOI: 10.1016/j.curtheres.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Efficacy, and Bioavailability of Fixed-Dose Combinations in Type 2 Diabetes Mellitus: A Systematic Updated Review

Abstract: PurposeType 2 diabetes mellitus (T2DM) is a multifactorial disease characterized by insulin resistance. As time progresses, monotherapy often does not provide effective glycemic control, generating the need for an add-on therapy. Hence, multiple oral hypoglycemic agents formulated as a single-dose form called fixed-dose combinations (FDCs) play an essential role in glycemic control. The purpose of this systematic review is to appraise the recently published evidence on the safety, efficacy, and bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Available studies support the wider use of FDC in the treatment of T2DM patients and the efficacy and safety of newer FDC seems to be promising and adds more treatment options. 43,44 The panel highlighted that, when prescribing and choosing the dual therapy option, the physician should consider drugspecific effect and patient factors. Atherosclerotic cardiovascular patients should take in combination to diabetic therapy a medication shown to reduce cardiovascular risks, two different SUs should not be combined, DPP-4i should not be combined with GLP-1RA and the insulin secretagogues such as SUs and meglitinides should be discontinued once insulin is introduced into a treatment regimen or at least within few months.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…Available studies support the wider use of FDC in the treatment of T2DM patients and the efficacy and safety of newer FDC seems to be promising and adds more treatment options. 43,44 The panel highlighted that, when prescribing and choosing the dual therapy option, the physician should consider drugspecific effect and patient factors. Atherosclerotic cardiovascular patients should take in combination to diabetic therapy a medication shown to reduce cardiovascular risks, two different SUs should not be combined, DPP-4i should not be combined with GLP-1RA and the insulin secretagogues such as SUs and meglitinides should be discontinued once insulin is introduced into a treatment regimen or at least within few months.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…Furthermore, nonadherence was also confirmed as an important contributor to the higher hospitalization rate and health care cost 20 . Currently, FDC is widely used in several chronic diseases such as hypertension, DM, and pulmonary tuberculosis to simplify treatment regimens, improving medication adherence and clinical outcomes 10,12,21‐24 . In our previous study, compared to the free combination of CCB/ARB, the FDC of amlodipine/valsartan improves MACE‐free survival, medication compliance, hospitalization rates, and also decreases total health care costs 12 .…”
Section: Discussionmentioning
confidence: 89%
“…In our previous study, compared to the free combination of CCB/ARB, the FDC of amlodipine/valsartan improves MACE‐free survival, medication compliance, hospitalization rates, and also decreases total health care costs 12 . The effect of FDC in the treatment of type 2 DM has been addressed in a systemic review including 10 studies, 2 of which were prospective, 1 was observational, and 7 were randomized, double‐blinded, parallel studies 21 . The authors concluded that the FDCs of various oral hypoglycemic agents significantly reduce glycated hemoglobin and fasting plasma glucose values, improve adherence, and reduce serious adverse drug reactions in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The dosing schedule of individual constituent of FDCs may differ and this may result in inflexible dosing regimen. There may be interaction among constituents of FDCs and this may result in adverse effects, particularly when drugs belonging to the same pharmacological class are used [4][5][6] . The increased number of prescriptions with FDCs is a matter of concern as it may develop irrational prescribing patterns in hospitals.…”
Section: Prescribing Trends and Rationality Of Fixed Dose Combinationmentioning
confidence: 99%